2020
DOI: 10.5435/jaaos-d-19-00276
|View full text |Cite
|
Sign up to set email alerts
|

The Return on Investment of Orthopaedic Fellowship Training: A Ten-year Update

Abstract: Background: Over 90% of graduating orthopaedic residents now pursue fellowship training, and only 15% of practicing orthopaedic surgeons now characterize themselves as generalists. Fellowship training has significant financial effects due to both opportunity cost of that year of training and changes in compensation throughout one's career. The purpose of this study was to estimate the financial return on investment by pursuing additional training in an orthopaedic fellowship versus general practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Recent studies suggest that more than 90% of graduating orthopaedic surgery residents complete at least 1 year of additional training and that 68% of open positions require fellowship training. 1 , 2 , 3 The San Francisco (SF) Match has facilitated the Orthopaedic Sports Medicine Fellowship Match annually since 2008. In 2019, there were 219 positions across 93 programs accredited by the American Orthopaedic Society for Sports Medicine and Arthroscopy Association of North America.…”
mentioning
confidence: 99%
“…Recent studies suggest that more than 90% of graduating orthopaedic surgery residents complete at least 1 year of additional training and that 68% of open positions require fellowship training. 1 , 2 , 3 The San Francisco (SF) Match has facilitated the Orthopaedic Sports Medicine Fellowship Match annually since 2008. In 2019, there were 219 positions across 93 programs accredited by the American Orthopaedic Society for Sports Medicine and Arthroscopy Association of North America.…”
mentioning
confidence: 99%
“…Correcting this trend may lead to more women pursuing orthopedics out of medical school. A number of studies have shown that women are more likely than men to indicate having a role model or mentor positively influences their pursuit of orthopedic surgery [6,7,[14][15][16][17][18]. On the other hand in January 2020, Bi et al found that 3/153 (2.0%) chairs and 18/161 (11.2%) of PDs were women in all residency programs, while our study found that 5/126 (4.0%) of chairs and 16/138 (11.6%) of PDs with an academic position were women as of March 2022 [4].…”
Section: Discussionmentioning
confidence: 99%
“…Easy online accessibility, content, and accreditation status of programs can influence objective parameters for candidates to investigate the program, thus potentially affecting their decision to apply and compose their rank list [16][17][18][19]. The selective application process may help decrease interview costs for the applicant as well as for the program [20][21][22][23][24]. Reputed programs (in terms of region, number of positions, accreditation, and affiliation with top medical school/residency program/hospital) may or may not be affected by online information availability.…”
Section: Discussionmentioning
confidence: 99%